Stem cell-based approaches in dentistry - TA Mitsiadis; G Orsini; L Jimenez-Rojo (European Cells & Materials, 2011)
Repair of dental pulp and periodontal lesions remains a major clinical challenge. Classical dental treatments require the use of specialised tissue-adapted materials with still questionable efficacy and durability. Stem cell-based therapeutic approaches could offer an attractive alternative in dentistry since they can promise physiologically improved structural and functional outcomes. These therapies necessitate a sufficient number of specific stem cell populations for implantation. Dental mesenchymal stem cells can be easily isolated and are amenable to in vitro expansion while retaining their stemness. In vivo studies realised in small and large animals have evidenced the potential of dental mesenchymal stem cells to promote pulp and periodontal regeneration, but have also underlined new important challenges. The homogeneity of stem cell populations and their quality control, the delivery method, the quality of the regenerated dental tissues and their integration to the host tissue are some of the key challenges. The use of bioactive scaffolds that can elicit effective tissue repair response, through activation and mobilisation of endogenous stem cell populations, constitutes another emerging therapeutic strategy. Finally, the use of stem cells and induced pluripotent cells for the regeneration of entire teeth represents a novel promising alternative to dental implant treatment after tooth loss. In this mini-review, we present the currently applied techniques in restorative dentistry and the various attempts that are made to bridge gaps in knowledge regarding treatment strategies by translating basic stem cell research into the dental practice.